2015
DOI: 10.1159/000373890
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Genetic Evidence for Shared Etiology of Autism and Prodigy

Abstract: Child prodigies are rare individuals with an exceptional working memory and unique attentional skills that may facilitate the attainment of professional skill levels at an age well before what is observed in the general population. Some characteristics of prodigy have been observed to be quantitatively similar to those observed in autism spectrum disorder (ASD), suggesting possible shared etiology, though objectively validated prodigies are so rare that evidence has been sparse. We performed a family-based gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 40 publications
0
4
0
1
Order By: Relevance
“…These participants scored on average significantly higher than the control group on the Autism Quotient questionnaire (AQ) (Baron-Cohen et al, 2001 ), but lower than the ASD group, except for the sub-category “attention to detail” which was higher than in the ASD group. Results from a second study (Ruthsatz et al, 2015 ) point to genetic evidence suggesting a shared etiology between ASD and “Prodigies.” According to this research, a locus on chromosome 1 could be related to the emergence of both autism and “prodigies” in a same family. These results are consistent with the high prevalence of ASD children found among the HIP group in the Doobay's study (Doobay et al, 2014 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These participants scored on average significantly higher than the control group on the Autism Quotient questionnaire (AQ) (Baron-Cohen et al, 2001 ), but lower than the ASD group, except for the sub-category “attention to detail” which was higher than in the ASD group. Results from a second study (Ruthsatz et al, 2015 ) point to genetic evidence suggesting a shared etiology between ASD and “Prodigies.” According to this research, a locus on chromosome 1 could be related to the emergence of both autism and “prodigies” in a same family. These results are consistent with the high prevalence of ASD children found among the HIP group in the Doobay's study (Doobay et al, 2014 ).…”
Section: Resultsmentioning
confidence: 99%
“…As in ASD, which is classified as a developmental disorder, certain HIP children have a developmental trajectory characterized by a degree of disharmony in the progression of different categories of acquisitions. From a genetic viewpoint, Ruthsatz et al ( 2015 ) have gone as far as suggesting a common etiology between ASD and “child prodigies” in their recent study.…”
Section: Discussionmentioning
confidence: 99%
“…Autism has been associated with high intellectual function (Crespi 2016), and it has been reported that the incidence of child prodigy is increased in families in which autism occurs (Ruthsatz and Urbach 2012). To follow up on this, a genome-wide linkage study was undertaken to identify loci that were associated with both autism and prodigy (Ruthsatz et al 2015). The strongest signal that was obtained was to a region on chr1 where the great majority of Olduvai copies map.…”
Section: Beneficial and Harmful Effects Of Olduvai Variationmentioning
confidence: 99%
“…There may be a genetic link between autism and gifted families that often produced autistic and/or ingenious children. Although it does not prove the direct causality between intelligence and ASD, it shows how complex this relation may be [19].…”
Section: Intellectual Functioningmentioning
confidence: 77%